Insecticide treated mosquito nets for malaria control in India-experience from a tribal area on operational feasibility and uptake - P Jambulingam; K Gunasekaran; SS Sahu; T Vijayakumar (Memorias do Instituto Oswaldo Cruz, 2008)
The study assessed the operational feasibility and acceptability of insecticide-treated mosquito nets (ITNs) in one Primary Health Centre (PHC) in a falciparum malaria endemic district in the state of Orissa, India, where 74% of the people are tribes and DDT indoor residual spraying had been withdrawn and ITNs introduced by the National Vector Borne Disease Control Programme. To a population of 63,920, 24,442 ITNs were distributed free of charge through 101 treatment centers during July-August 2002. Interview of 1,130, 1,012 and 126 respondents showed that the net use rates were 80%, 74% and 55% in the cold, rainy and summer seasons, respectively. Since using ITNs, 74.5-76.6% of the respondents observed reduction of mosquito bites and 7.2-32.1% reduction of malaria incidence; 37% expressed willingness to buy ITNs if the cost was lower and they were affordable. Up to ten months post-treatment, almost 100% mortality of vector mosquitoes was recorded on unwashed and washed nets (once or twice). Health workers re-treated the nets at the treatment centers eight months after distribution on a cost-recovery basis. The coverage reported by the PHC was only 4.2%, mainly because of unwillingness of the people to pay for re-treatment and to go to the treatment centers from their villages. When the re-treatment was continued at the villages involving personnel from several departments, the coverage improved to about 90%.Interview of 126 respondents showed that among those who got their nets re-treated, 81.4% paid cash for the re-treatment and the remainder were reluctant to pay. Majority of those who paid said that they did so due to the fear that if they did not do so they would lose benefits from other government welfare schemes. The 2nd re-treatment was therefore carried out free of charge nine months after the 1st re-treatment and thus achieved coverage of 70.4%. The study showed community acceptance to use ITNs as they perceived the benefit. Distribution and re-treatment of nets was thus possible through the PHC system, if done free of charge and when personnel from different departments, especially those at village level, were involved.